Two ways to consider atmospheric turbulences in FSO propagation - Fišer Ondřej; Brázda Vladimír; Rejfek Luboš (IEEE (Institute of Electrical and Electronics Engineers), 2014)
Summary of investigation of impact of both wind parameters as well as structure index on FSO attenuation through turbulences is given. It is followed by the direct looking for correlation between chosen wind parameters and structure index. We concluded that west-east component of the wind velocity vector, vertical turbulent heat flow, weighted standard deviation of the vertical wind speed component and 3D intensity of turbulence can replace the structure index in order to estimate the FSO link attenuation through atmospheric turbulences.
Dva způsoby měření atmosférických turbulencí v šíření FSO
Keywords: FSO link; attenuation; atmospheric turbulence; wind parameters; structure index; Optický bezdrátový spoj; útlum; atmosférické turbulence; větrné turbulence; strukturní index